Experimental Assessment of Mining Waste Utilization in Cementitious Construction Materials: Strength, Water Absorption, and Durability Performance - Ranggu, Ruth Bunga; Sani, Hendra; Sumbung, Dwi Yolanda (Program Studi Teknik Komputer, 2026)
Purpose – This study aims to comparatively evaluate the potential of three Indonesian mining and industrial waste streams gold-mine tailings, ferronickel slag, and coal fly ash for utilization in cementitious materials within a unified experimental framework, supporting sustainable construction and circular economy strategies. Design/methods/approach – A screening-level experimental design was applied by incorporating tailings as a 10% fine-aggregate replacement, and ferronickel slag and fly ash as 10% cement replacements. Performance was assessed using compressive strength, water absorption, and durability-related behavior under 28 days of 5% NaCl immersion, with conventional concrete as a control. Statistical analysis included one-way ANOVA and Tukey HSD, alongside pooled correlation analysis. Findings – Results indicate that waste type significantly influences performance. The slag mixture (S-10) achieved the best balance, with a 28-day compressive strength of 28.93 MPa (90.32% of control), low water absorption (4.50%), and a “Good” durability rating. Tailings-based concrete showed moderate performance, while the fly-ash mixture exhibited the weakest chloride resistance. Statistical tests confirmed significant differences across all groups (p < 0.05), and a strong inverse correlation between compressive strength and water absorption (r = −0.798, p = 0.0019). Research implications/limitations – The study provides initial comparative insights but is limited by its exploratory NaCl immersion method and absence of advanced characterization (XRF, XRD, SEM) and leaching analysis, restricting mechanistic and environmental interpretation. Originality/value – This research contributes a novel comparative framework by evaluating multiple waste streams and utilization pathways under a standardized protocol, offering practical screening evidence to guide material selection in sustainable construction